On the mechanism of miR-29b enhancement of etoposide toxicity in vitro - Dostál, Zdeněk; Buchtíková, Jana; Mandrla, Jan; Modrianský, Martin (Scientific reports, 2024)
MicroRNA hsa-miR-29 was connected to a number of malignancies. Its target genes are many, among them Mcl-1 that is expressed in three possible isoforms, one of which is anti-apoptotic and another one pro-apoptotic. Ratio of these two isoforms appears to affect cell response to external stimuli. We have demonstrated that miR-29b enhanced etoposide toxicity in HeLa cell line by modulating this ratio of Mcl-1 isoforms. However, it is not known whether the described miR-29 effect is common to various cancer types or even have the opposite effect. This represents a significant problem for possible future applications. In this report, we demonstrate that miR-29b affects toxicity of 60 μM etoposide in cell lines derived from selected malignancies. The mechanism, however, differs among the cell lines tested. Hep G2 cells demonstrated similar effect of miR-29b on etoposide toxicity as was described in HeLa cells, i.e. modulation of Mcl-1 expression. Target protein down-regulated by miR-29b resulting in enhanced etoposide toxicity in Caco-2 cells was, however, Bcl-2 protein. Moreover, H9c2, Hek-293 and ARPE-19 cell lines selected as a representatives of non-malignant cells, showed no effect of miR-29b on etoposide toxicity. Our data suggest that miR-29b could be a common enhancer of etoposide toxicity in malignant cells due to its modulation of Bcl family proteins.
Keywords: MicroRNAs; Antineoplastic Agents, Phytogenic; HEK293 buňky; buňky Hep G2; mikro RNA; Myeloid Cell Leukemia Sequence 1 Protein; HEK293 Cells; etoposid; HeLa buňky; lidé; HeLa Cells; Humans; Caco-2 Cells; Hep G2 Cells; Caco-2 buňky; apoptóza; protoonkogenní proteiny c-bcl-2; Proto-Oncogene Proteins c-bcl-2; fytogenní protinádorové látky; Apoptosis; Etoposide; protein MCL-1